(untitled) (Journal of Pharmaceutical Negative Results, 2014)
Aims: The aim was to determine antimicrobial and anticancer activities for water and ethanolextracts of leaves and shooting parts of seablite. Materials and Methods: Anticanceractivity tests of seablite extracts were performed by resazurin microplate assay (REMA)and tested with 3 cell lines including KB cell line, epidermoid carcinoma of the oralcavity (American Type Culture Collection [ATCC] CCL‑17), MCF‑7 cell line,breast adenocarcinoma (ATCC HTB‑22) and NCI‑H187 cell line, and small cell lungcarcinoma (ATCC CRL‑5804). Antimicrobial activities of seablite water and ethanolextracts against herpes simplex virus type‑I (HSV‑1) and Mycobacterium tuberculosisH37Ra strain were tested according by green fluorescent protein‑based assay; Candidaalbicans (ATCC 90028) and Bacillus cereus (ATCC 11778 or TISTR 687) were testedaccording by REMA; and Plasmodium falciparum, K1 strain was tested according bymicro‑culture radioisotope techniques. Results: Both extracts were not possessedanticancer activity to KB‑oral cavity cancer, MCF7‑breast cancer and NCI‑H187‑smalllung cancer cell lines at maximum concentration = 50 µg/mL. In the same wayto anticancer activity assays, both extracts were not inhibited HSV‑1, P. falciparumK1 strain, M. tuberculosis H37Ra strain and B. cereus at the same concentration.Conclusions: Ethanol and water extracts of leaves and shooting parts of seablite hadno significant anticancer and antimicrobial activities.